Toughened carbon nanofiber membrane as well as preparation method and application thereof in gas purification
Through electrospinning and heat treatment technology, toughened carbon nanofiber membranes with high flexibility and porous structures were prepared, which solved the brittleness of carbon nanofiber membranes and achieved efficient gas purification applications.
Patent Information
- Application Number
- CN202411430591.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Due to its brittleness, carbon nanofiber membranes are prone to stress concentration under external forces and cause material damage, which limits its application range.
Toughened carbon nanofiber membranes were prepared by electrospinning combined with heat treatment program, and the spinning was prepared by mixing epoxy resin, polyarylene ethernitrile, polyvinylpyrrolidone, terephthalic acid, carbon nanotubes, polyacrylonitrile and solvents. The wire solution was subjected to pre-oxidation and carbonization after electrospinning to form a toughened carbon nanofiber membrane with a porous structure and a high specific surface area.
The flexibility of carbon nanofiber membranes has been improved, and the tensile fracture stress has been increased from 0.42MPa to 8.44MPa, an increase of 19.1 times. At the same time, it maintains a rich porous structure and high specific surface area, which is suitable for gas purification and other fields.
Smart Images

Figure CN119392439A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a toughened carbon nanofiber membrane and a preparation method thereof and application in gas purification, belonging to the technical field of membrane material preparation. Background Art
[0002] In recent years, carbon nanofiber membranes have been increasingly used in the fields of air purification, sewage treatment, energy storage, sound absorption, catalytic degradation, etc. due to their high specific surface area, easy structure control, light weight, and good thermal / chemical stability. However, carbon nanofiber membranes are often brittle and prone to stress concentration under external forces, resulting in material damage. Therefore, poor flexibility limits the application of carbon nanofiber membranes.
[0003] Electrospinning is a classic method for preparing nanofiber materials. It is a spinning technology with simple equipment, convenient operation, and short preparation cycle. It has the advantages of adjustable fiber diameter and diverse fiber morphology. The nanofibers prepared by electrospinning are stabilized in the air and then carbonized in a protective atmosphere at a certain temperature to prepare carbon nanofiber membranes. During the carbonization process, the content of non-carbon atoms decreases and the carbon content of the fiber membrane increases. Due to the reorganization of the molecular structure after carbonization, the graphite carbon structure increases, and the fiber becomes brittle.
[0004] Generally, the introduction of porous structures can effectively disperse stress and avoid stress concentration causing fiber breakage and membrane damage. Yan et al. used the above principle to prepare BFN triple-doped flexible porous carbon nanofibers through electrospinning and oxidative pyrolysis processes, which have controllable porous structures and about 750m 2 / g high surface area, its tensile fracture stress can reach 2.23MPa, and the corresponding elongation is 0.52% (see Yan J, Dong K, Zhang Y, et al. Multifunctional flexible membranes from sponge-like porous carbon nanofibers with high conductivity [J]. Nature Communications, 2019, 10 (1): 5584).
[0005] Particle doping can also effectively toughen the surface. After adding nanoparticles, the boundary can be strengthened to increase the length of the crack path. The stress intensity near the crack tip is reduced, and the residual stress field and microcracks formed at the same time cause the deviation of the crack path. Song et al. used the above principle to incorporate TiO2 NPs into a carbon matrix to prepare a highly flexible TiO2 / C nanofiber membrane. The TiO2 / C nanofiber membrane withstood bending deformation and showed excellent bending stability (see document Song L, Yin X, Xie X, et al. Highly flexible TiO2 / C nanofibrous film for flexible dye-sensitized solar cells as a platinum-and transparent conducting oxide-free flexible counter electrode [J]. Electrochimica Acta, 2017, 255: 256-265).
[0006] The above methods have obvious toughening effects, and the fracture stress can reach 1 to 3 MPa, but it is difficult to further improve the toughness of carbon nanofiber membranes. Summary of the invention
[0007] The purpose of the present invention is to provide a toughened carbon nanofiber membrane, a preparation method thereof and an application in gas purification. The carbon nanofiber membrane prepared by this method can reduce stress concentration, improve flexibility, and can be freely formed and cut; at the same time, it also has a rich porous structure and a high specific surface area, and can efficiently purify PM and VOCs.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A method for preparing a toughened carbon nanofiber membrane comprises the following steps: firstly, epoxy resin, polyarylene ether nitrile, polyvinyl pyrrolidone, terephthalic acid, carbon nanotubes, polyacrylonitrile and a solvent are mixed to prepare a spinning solution, and then electrospinning is performed to obtain a precursor nanofiber membrane; then, the precursor nanofiber membrane is pre-oxidized and then carbonized to obtain a nanofiber membrane having a porous structure (including micropores and mesopores) and a large surface area (613m 2 / g) of toughened carbon nanofiber membrane. The toughened carbon nanofiber membrane can be bent and cut freely, can withstand 180° bending without breaking, has a high tensile fracture stress of up to 8.99MPa, and at this time the tensile strain can reach 1.99%.
[0010] Preferably, the mass ratio of epoxy resin, polyarylene ether nitrile, polyvinyl pyrrolidone, terephthalic acid, carbon nanotubes, polyacrylonitrile and solvent is (0.5-2):(1-5):(2-6):(2-7):(0.1-0.5):(5-10):(80-150); the preferred range is (0.8-1):(1-3):(2-3):(2-3):(0.2-0.3):(7-9):(95-110).
[0011] Preferably, the molecular weight of polyacrylonitrile is 1×10 5 -2×10 5 ; The solvent is DMF.
[0012] Preferably, the preparation method of the spinning solution is as follows: first, carbon nanotubes are added to the solvent and ultrasonically dispersed for 20-50 minutes; then, epoxy resin, polyarylene ether nitrile, polyvinyl pyrrolidone, terephthalic acid and polyacrylonitrile are added in sequence under constant temperature stirring at 70-90°C, and stirring is continued for 2-5 hours.
[0013] Preferably, the conditions for electrospinning are: voltage 15-20 kV, receiving distance 12-20 cm, receiver speed 30-100 rpm, translation speed 80-120 mm / min, stroke 50-150 mm, spinning solution push rate in each syringe 0.5-2 ml / h, temperature 20-35° C., and humidity 20-35%.
[0014] Preferably, after the precursor nanofiber membrane is obtained by electrospinning, a drying step is performed, and the drying conditions are: 50-80° C., 10-15 h.
[0015] Preferably, the specific method of pre-oxidation is: in an air atmosphere, heating to 250-300°C at a heating rate of 0.5-3°C / min, keeping the temperature for 1-4 hours and then cooling to room temperature;
[0016] The specific method of carbonization treatment is: in a nitrogen or inert gas atmosphere, heat up to 320-350°C at a heating rate of 3-8°C / min, keep warm for 1-3h; then heat up to 780-850°C at a heating rate of 3-8°C / min, keep warm for 1-3h and then cool to room temperature.
[0017] A toughened carbon nanofiber membrane is prepared by any of the above methods.
[0018] The toughened carbon nanofiber membrane prepared by any of the above methods is used in gas purification, including the purification of PM and VOCs in the air.
[0019] A method for increasing the specific surface area and / or the adsorption amount of VOC and / or the filtering efficiency of PM pollutants of a carbon nanofiber membrane, comprising the following steps: firstly mixing epoxy resin, polyarylene ether nitrile, polyvinyl pyrrolidone, terephthalic acid, carbon nanotubes, polyacrylonitrile and a solvent to prepare a spinning solution, and then electrospinning to obtain a precursor nanofiber membrane; then pre-oxidizing the precursor nanofiber membrane and then carbonizing it to obtain a toughened carbon nanofiber membrane;
[0020] The mass ratio of epoxy resin, polyarylene ether nitrile, polyvinyl pyrrolidone, terephthalic acid, carbon nanotubes, polyacrylonitrile and solvent is (0.5-2):(1-5):(2-6):(2-7):(0.1-0.5):(5-10):(80-150), and the preferred range is (0.8-1.2):(1-3):(2-4):(2-4):(0.2-0.4):(7-9):(95-110).
[0021] The beneficial effects of the present invention are:
[0022] The carbon nanofiber membrane is prepared by electrospinning combined with a heat treatment procedure. Polyacrylonitrile is used as a carbon source, and polyvinyl pyrrolidone, terephthalic acid, epoxy resin, polyarylene ether nitrile, and multi-walled carbon nanotubes are added to obtain a porous structure, increase the content of disordered carbon, and increase interlayer interaction to reduce stress concentration, thereby achieving a toughening effect.
[0023] Compared with traditional carbon nanofibers, the carbon nanofiber membrane prepared by the present invention can be bent and cut freely, has ultra-high tensile properties, and the tensile fracture stress is increased from 0.42MPa to 8.44MPa, which is increased by 19.1 times; at the same time, it has a rich porous structure with a high specific surface area (613m 2 / g), which has practical application value in many fields, including the purification of PM and VOCs. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM image of the toughened flexible carbon nanofiber membrane (FCNFM) of Example 1;
[0025] Figure 2 is a SEM image of the untoughened carbon nanofiber membrane (CNFM) of Comparative Example 1;
[0026] Figure 3 is a SEM image of the carbon nanofiber membrane of Comparative Example 2;
[0027] Figure 4 is a SEM image of the carbon nanofiber membrane of Comparative Example 3;
[0028] Figure 5180° bending test images of the untoughened carbon nanofiber membrane in Comparative Example 1 and the toughened flexible carbon nanofiber membrane (FCNFM) in Example 1;
[0029] Figure 6 The stress-strain images of the carbon nanofiber membranes of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3;
[0030] Figure 7 Raman images of the untoughened carbon nanofiber membrane (CNFM) in Comparative Example 1 and the toughened flexible carbon nanofiber membrane (FCNFM) in Example 1;
[0031] Figure 8 The nitrogen adsorption / desorption isotherms of the untoughened carbon nanofiber membrane (CNFM) in Comparative Example 1 and the toughened flexible carbon nanofiber membrane (FCNFM-X) in Examples 1, 2, and 3, where X is the amount of PTA added;
[0032] Fig. 9 It is a numerical comparison chart of the specific surface area of the untoughened carbon nanofiber membrane (CNFM) in Comparative Example 1 and the toughened flexible carbon nanofiber membrane (FCNFM-X) in Examples 1, 2, and 3, where X is the amount of PTA added;
[0033] Fig.10 It is a comparison chart of the VOCs adsorption performance of the untoughened carbon nanofiber membrane (CNFM) in Comparative Example 1 and the toughened flexible carbon nanofiber membrane (FCNFM-X) in Examples 1, 2, and 3, where X is the amount of PTA added;
[0034] Fig.11 It is a comparison chart of the filtration efficiency of the untoughened carbon nanofiber membrane (CNFM) in Comparative Example 1 and the toughened flexible carbon nanofiber membrane (FCNFM-X) in Examples 1, 2, and 3;
[0035] Fig.12 It is a comparison diagram of the pressure drop of the untoughened carbon nanofiber membrane (CNFM) in Comparative Example 1 and the toughened flexible carbon nanofiber membrane (FCNFM-X) in Examples 1, 2, and 3;
[0036] Fig.13 It is a comparison chart of the quality factors of the untoughened carbon nanofiber membrane (CNFM) in Comparative Example 1 and the toughened flexible carbon nanofiber membrane (FCNFM-X) in Examples 1, 2, and 3. DETAILED DESCRIPTION
[0037] Example 1
[0038] (1) Preparation of spinning solution: 15 mg of multi-walled carbon nanotubes were put into 5 mL of N,N-dimethylformamide and ultrasonically dispersed for 30 minutes. Then, 50 mg of epoxy resin (EP), 100 mg of polyarylene ether nitrile (PEN), 100 mg of polyvinyl pyrrolidone (PVP), 100 mg of terephthalic acid (PTA), 400 mg of polyacrylonitrile (PAN, M) were added in sequence under constant temperature stirring at 80 °C. W =150000), and stirred at constant temperature for 4h.
[0039] (2) Preparation of precursor nanofiber membrane by electrospinning: 2 mL of spinning solution was sucked in two syringes in turn, and the two syringes were assembled into an electrospinning device. The speed of each syringe in the device to extrude the spinning solution was 1 mL / h, the spinning needle model was 21G, the receiving distance was 17 cm, the spinning voltage was 17.5 kV, the spinning time was 2 h, the temperature was 25 ° C, and the humidity was 30%. The obtained precursor nanofiber membrane was placed in a 60 ° C oven and dried for 12 h.
[0040] (3) Pre-oxidation: The precursor nanofiber membrane is placed in a muffle furnace, heated to 260°C at a heating rate of 1°C / min in an air atmosphere, and kept at this temperature for 2 h to obtain a pre-oxidized precursor nanofiber membrane.
[0041] (4) Carbonization: The pre-oxidized precursor nanofiber membrane was placed in a tubular quartz furnace, heated to 335°C at a heating rate of 5°C / min under a N2 atmosphere, and kept warm for 2 h. The temperature was then further increased to 800°C at a heating rate of 5°C / min and kept warm for 2 h to obtain a toughened flexible carbon nanofiber membrane.
[0042] Example 2
[0043] (1) Preparation of spinning solution: 15 mg of multi-walled carbon nanotubes were put into 5 mL of N,N-dimethylformamide and ultrasonically dispersed for 30 minutes. Then, 50 mg of epoxy resin (EP), 100 mg of polyarylene ether nitrile (PEN), 100 mg of polyvinyl pyrrolidone (PVP), 150 mg of terephthalic acid (PTA), 400 mg of polyacrylonitrile (PAN, M W =150000), and stirred at constant temperature for 4h.
[0044] (2) Preparation of precursor nanofiber membrane by electrospinning: 2 mL of spinning solution was sucked in two syringes in turn, and the two syringes were assembled into an electrospinning device. The speed of each syringe in the device to extrude the spinning solution was 1 mL / h, the spinning needle model was 21G, the receiving distance was 17 cm, the spinning voltage was 17.5 kV, the spinning time was 2 h, the temperature was 25 ° C, and the humidity was 30%. The obtained precursor nanofiber membrane was placed in a 60 ° C oven and dried for 12 h.
[0045] (3) Pre-oxidation: The precursor nanofiber membrane is placed in a muffle furnace, heated to 260°C at a heating rate of 1°C / min in an air atmosphere, and kept at this temperature for 2 h to obtain a pre-oxidized precursor nanofiber membrane.
[0046] (4) Carbonization: The pre-oxidized precursor nanofiber membrane was placed in a tubular quartz furnace, heated to 335°C at a heating rate of 5°C / min under a N2 atmosphere, and kept warm for 2 h. The temperature was then further increased to 800°C at a heating rate of 5°C / min and kept warm for 2 h to obtain a toughened flexible carbon nanofiber membrane.
[0047] Example 3
[0048] (1) Preparation of spinning solution: 15 mg of multi-walled carbon nanotubes were put into 5 mL of N,N-dimethylformamide and ultrasonically dispersed for 30 minutes. Then, 50 mg of epoxy resin (EP), 100 mg of polyarylene ether nitrile (PEN), 100 mg of polyvinyl pyrrolidone (PVP), 200 mg of terephthalic acid (PTA), 400 mg of polyacrylonitrile (PAN, M W =150000), and stirred at constant temperature for 4h.
[0049] (2) Preparation of precursor nanofiber membrane by electrospinning: 2 mL of spinning solution was sucked in two syringes in turn, and the two syringes were assembled into an electrospinning device. The speed of each syringe in the device to extrude the spinning solution was 1 mL / h, the spinning needle model was 21G, the receiving distance was 17 cm, the spinning voltage was 17.5 kV, the spinning time was 2 h, the temperature was 25 ° C, and the humidity was 30%. The obtained precursor nanofiber membrane was placed in a 60 ° C oven and dried for 12 h.
[0050] (3) Pre-oxidation: The precursor nanofiber membrane is placed in a muffle furnace, heated to 260°C at a heating rate of 1°C / min in an air atmosphere, and kept at this temperature for 2 h to obtain a pre-oxidized precursor nanofiber membrane.
[0051] (4) Carbonization: The pre-oxidized precursor nanofiber membrane was placed in a tubular quartz furnace, heated to 335°C at a heating rate of 5°C / min under a N2 atmosphere, and kept warm for 2 h. The temperature was then further increased to 800°C at a heating rate of 5°C / min and kept warm for 2 h to obtain a toughened flexible carbon nanofiber membrane.
[0052] Example 4
[0053] (1) Preparation of spinning solution: 15 mg of multi-walled carbon nanotubes were put into 5 mL of N,N-dimethylformamide and ultrasonically dispersed for 30 minutes. Then, 50 mg of epoxy resin (EP), 100 mg of polyarylene ether nitrile (PEN), 150 mg of polyvinyl pyrrolidone (PVP), 150 mg of terephthalic acid (PTA), and 400 mg of polyacrylonitrile (PAN, M) were added in sequence under constant temperature stirring at 80 °C. W =150000), and stirred at constant temperature for 4h.
[0054] (2) Preparation of precursor nanofiber membrane by electrospinning: 2 mL of spinning solution was sucked in two syringes in turn, and the two syringes were assembled into an electrospinning device. The speed of each syringe in the device to extrude the spinning solution was 1 mL / h, the spinning needle model was 21G, the receiving distance was 17 cm, the spinning voltage was 17.5 kV, the spinning time was 2 h, the temperature was 25 ° C, and the humidity was 30%. The obtained precursor nanofiber membrane was placed in a 60 ° C oven and dried for 12 h.
[0055] (3) Pre-oxidation: The precursor nanofiber membrane is placed in a muffle furnace, heated to 260°C at a heating rate of 2°C / min in an air atmosphere, and kept at this temperature for 2 h to obtain a pre-oxidized precursor nanofiber membrane.
[0056] (4) Carbonization: The pre-oxidized precursor nanofiber membrane was placed in a tubular quartz furnace, heated to 335°C at a heating rate of 5°C / min under a N2 atmosphere, and kept warm for 2 h. The temperature was then further increased to 800°C at a heating rate of 5°C / min and kept warm for 2 h to obtain a toughened flexible carbon nanofiber membrane.
[0057] Example 5
[0058] (1) Preparation of spinning solution: 15 mg of multi-walled carbon nanotubes were put into 5 mL of N,N-dimethylformamide and ultrasonically dispersed for 30 minutes. Then, 50 mg of epoxy resin (EP), 100 mg of polyarylene ether nitrile (PEN), 200 mg of polyvinyl pyrrolidone (PVP), 150 mg of terephthalic acid (PTA), and 400 mg of polyacrylonitrile (PAN, M) were added in sequence under constant temperature stirring at 80 °C. W =150000), and stirred at constant temperature for 4h.
[0059] (2) Preparation of precursor nanofiber membrane by electrospinning: 2 mL of spinning solution was sucked in two syringes in turn, and the two syringes were assembled into an electrospinning device. The speed of each syringe in the device to extrude the spinning solution was 1 mL / h, the spinning needle model was 21G, the receiving distance was 17 cm, the spinning voltage was 17.5 kV, the spinning time was 2 h, the temperature was 25 ° C, and the humidity was 30%. The obtained precursor nanofiber membrane was placed in a 60 ° C oven and dried for 12 h.
[0060] (3) Pre-oxidation: The precursor nanofiber membrane is placed in a muffle furnace, heated to 260°C at a heating rate of 1°C / min in an air atmosphere, and kept at this temperature for 2 h to obtain a pre-oxidized precursor nanofiber membrane.
[0061] (4) Carbonization: The pre-oxidized precursor nanofiber membrane was placed in a tubular quartz furnace, heated to 335°C at a heating rate of 5°C / min under a N2 atmosphere, kept warm for 2 h, and then continued to heat to 800°C at a heating rate of 8°C / min and kept warm for 2 h to obtain a toughened flexible carbon nanofiber membrane.
[0062] Comparative Example 1
[0063] (1) Preparation of spinning solution: 400 mg of polyacrylonitrile was added to 5 mL of N,N-dimethylformamide, dispersed by ultrasonic for 30 min, and stirred at 80 °C for 4 h.
[0064] (2) Electrospinning to prepare precursor nanofiber membrane: 2 mL of spinning solution was drawn into two syringes in turn, and the two syringes were assembled into an electrospinning device. The speed of each syringe in the device to extrude the spinning solution was 1 mL / h. -1 The spinning needle model is 21G, the receiving distance is 17 cm, the spinning voltage is 17.5 kV, the spinning time is 2 h, the temperature is 25 ° C, and the humidity is 30%. The obtained precursor nanofiber membrane is placed in a 60 ° C oven for 12 h.
[0065] (3) Pre-oxidation: The precursor nanofiber membrane was placed in a muffle furnace under air atmosphere at 1°C min -1 The temperature was raised to 260°C at a heating rate of , and kept at that temperature for 2h to obtain the pre-oxidized precursor nanofiber membrane.
[0066] (4) Carbonization: The pre-oxidized precursor nanofiber membrane was placed in a tubular quartz furnace and heated at 5 °C min under a N2 atmosphere. -1 The temperature was raised to 335°C at a rate of 5°C·min -1 The temperature was raised to 800°C at a heating rate of and kept at that temperature for 2 h to obtain an untoughened carbon nanofiber membrane.
[0067] Comparative Example 2
[0068] (1) Preparation of spinning solution: 15 mg of multi-walled carbon nanotubes were put into 5 mL of N,N-dimethylformamide and ultrasonically dispersed for 30 minutes. Then, 50 mg of epoxy resin (EP), 100 mg of polyarylene ether nitrile (PEN), 100 mg of terephthalic acid (PTA), 400 mg of polyacrylonitrile (PAN, M) were added in sequence under constant temperature stirring at 80 °C. W =150000), and stirred at constant temperature for 4h.
[0069] (2) Preparation of precursor nanofiber membrane by electrospinning: 2 mL of spinning solution was sucked in two syringes in turn, and the two syringes were assembled into an electrospinning device. The speed of each syringe in the device to extrude the spinning solution was 1 mL / h, the spinning needle model was 21G, the receiving distance was 17 cm, the spinning voltage was 17.5 kV, the spinning time was 2 h, the temperature was 25 ° C, and the humidity was 30%. The obtained precursor nanofiber membrane was placed in a 60 ° C oven and dried for 12 h.
[0070] (3) Pre-oxidation: The precursor nanofiber membrane is placed in a muffle furnace, heated to 260°C at a heating rate of 1°C / min in an air atmosphere, and kept at this temperature for 2 h to obtain a pre-oxidized precursor nanofiber membrane.
[0071] (4) Carbonization: The pre-oxidized precursor nanofiber membrane was placed in a tubular quartz furnace, heated to 335°C at a heating rate of 5°C / min under a N2 atmosphere, and kept warm for 2 h. The temperature was then further increased to 800°C at a heating rate of 5°C / min and kept warm for 2 h to obtain a toughened flexible carbon nanofiber membrane.
[0072] Comparative Example 3
[0073] (1) Preparation of spinning solution: 15 mg of multi-walled carbon nanotubes were placed in 5 mL of N,N-dimethylformamide and ultrasonically dispersed for 30 minutes. Then, 50 mg of epoxy resin (EP), 100 mg of polyarylene ether nitrile (PEN), 100 mg of polyvinyl pyrrolidone (PVP), 400 mg of polyacrylonitrile (PAN, M) were added in sequence under constant temperature stirring at 80 °C. W =150000), and stirred at constant temperature for 4h.
[0074] (2) Preparation of precursor nanofiber membrane by electrospinning: 2 mL of spinning solution was sucked in two syringes in turn, and the two syringes were assembled into an electrospinning device. The speed of each syringe in the device to extrude the spinning solution was 1 mL / h, the spinning needle model was 21G, the receiving distance was 17 cm, the spinning voltage was 17.5 kV, the spinning time was 2 h, the temperature was 25 ° C, and the humidity was 30%. The obtained precursor nanofiber membrane was placed in a 60 ° C oven and dried for 12 h.
[0075] (3) Pre-oxidation: The precursor nanofiber membrane is placed in a muffle furnace, heated to 260°C at a heating rate of 1°C / min in an air atmosphere, and kept at this temperature for 2 h to obtain a pre-oxidized precursor nanofiber membrane.
[0076] (4) Carbonization: The pre-oxidized precursor nanofiber membrane was placed in a tubular quartz furnace, heated to 335°C at a heating rate of 5°C / min under a N2 atmosphere, and kept warm for 2 h. The temperature was then further increased to 800°C at a heating rate of 5°C / min and kept warm for 2 h to obtain a toughened flexible carbon nanofiber membrane.
[0077] Figures 1 to 4 The SEM images of the carbon nanofiber membranes of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 respectively show that a large number of micropores appear on the fiber surfaces of Example 1 and Comparative Example 2 with the addition of PTA. This is because PTA sublimates during the heat treatment process.
[0078] Figure 5 These are the 180° bending test images of the untoughened carbon nanofiber membrane in Comparative Example 1 and the toughened flexible carbon nanofiber membrane in Example 1. The untoughened carbon nanofiber membrane is brittle and breaks after being bent 180°, while the toughened flexible carbon nanofiber membrane returns to its original shape after being bent 180° without obvious cracks, indicating that it has high flexibility.
[0079] Figure 6 The stress-strain images of the carbon nanofiber membranes of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 show that the strain of Comparative Example 2 is significantly increased compared to Comparative Example 1, and the fracture stress of Comparative Example 3 is greatly increased, indicating that the addition of PTA and PVP increases the strain and fracture stress respectively. The fracture stress of the toughened carbon nanofiber membrane of Example 1 increases from 0.42MPa to 8.44MPa, an increase of 19.1 times, and the elongation at break increases from 0.15% to 1.79%, an increase of 10.9 times, indicating that the carbon nanofiber membrane has high flexibility and has practical application value.
[0080] Figure 7 The Raman images of the untoughened carbon nanofiber membrane (CNFM) in Comparative Example 1 and the toughened flexible carbon nanofiber membrane (FCNFM) in Example 1; the D peak represents disordered carbon, the G peak represents graphite carbon, and the I peak represents graphite carbon. D / I G The value increased from 1.05 to 1.24, indicating that the disorder of carbon atoms in the fiber microstructure increased, further verifying the mechanism of fiber toughening. The reduction in the proportion of graphite carbon improved the toughness of the carbon fiber membrane.
[0081] Figure 8 and Fig. 9The nitrogen adsorption / desorption isotherms and specific surface area values of the untoughened carbon nanofiber membrane (CNFM) in comparative example 1 and the toughened flexible carbon nanofiber membrane (FCNFM-X) in examples 1, 2, and 3 are compared, where X is the amount of PTA added. The nitrogen adsorption / desorption isotherms of CNFM and FCNFM are both type I, indicating that the microstructure is mainly composed of micropores. Moreover, with the increase of PTA content, the volume of micropores generated by PTA sublimation increases, and the nitrogen adsorption amount and specific surface area of FCNFM increase significantly. Among them, the specific surface area of FCNFM-200 can reach 613m 2 ·g -1 .
[0082] Fig.10 This is a comparison chart of the VOCs adsorption performance of the untoughened carbon nanofiber membrane (CNFM) in Comparative Example 1 and the toughened flexible carbon nanofiber membrane (FCNFM-X) in Examples 1, 2, and 3. Two typical VOCs, toluene and formaldehyde, were selected as target pollutants. Pure toluene or formaldehyde solution was added to a sealed container, and the adsorbent was placed in a sealed container for adsorption for 24 hours. The static adsorption capacity was calculated by weighing method. The adsorption performance of FCNFM increased significantly after adding PTA, and the static adsorption capacity of toluene and formaldehyde reached 182.8-394.4 mg·g -1 , and the adsorption amount increases with the increase of PTA content. The increase in specific surface area of carbon nanofiber membrane improves the adsorption performance. The porous structure can be regulated by adjusting the content of PTA, thereby controlling the adsorption performance of the membrane.
[0083] Fig.11 , Fig.12 and Fig.13 The filtration efficiency, pressure drop and quality factor comparison diagram of the untoughened carbon nanofiber membrane (CNFM) in comparative example 1 and the toughened flexible carbon nanofiber membrane (FCNFM-X) in examples 1, 2 and 3 were tested using an automatic filter material tester (TSI 8130). The target pollutants were PM 2.5 and PM 0.3 . When the air velocity is 5.33cm·s -1 Under the condition of 0.3 The filtration efficiency is only 82.51%, which is obviously not enough to meet the requirements of high-efficiency filtration of PM 0.3 , while FCNFM-100, FCNFM-150, FCNFM-200 have requirements for PM 0.3The filtration efficiency of FCNFM-200 is 99.93%, 99.93% and 99.53%. The improvement of flexibility makes the fiber less likely to break at a certain wind speed, which improves the filtration efficiency. However, as the amount of PTA added continues to increase, the pore size continues to increase, causing some particles to penetrate the fiber membrane with the airflow, so the filtration efficiency of FCNFM-200 is reduced. All samples have a good effect on PM 2.5 All of them have extremely high filtration efficiency. The filtration efficiency of FCNFM-100, FCNFM-150 and FCNFM-200 are 99.95%, 99.99% and 99.98% respectively. Even the filtration efficiency of CNFM for PM2.5 is as high as 98.9%, which also reflects the potential of carbon nanofiber membrane as a high-performance filtration material.
[0084] Pressure drop is an important parameter for evaluating the filtration performance of materials. It is the pressure loss after air flows through the filter. Reducing the pressure drop can improve the comfort of wearing a mask and reduce the difficulty in breathing or chest tightness caused by wearing a respiratory protective mask for a long time. Fig.12 As shown in the figure, with the increase of PTA content, the pressure drop of carbon nanofiber membrane is significantly reduced, which are 195.5Pa, 136.2Pa, 82.0Pa, and 33.3Pa respectively. Usually, filtration efficiency and pressure drop are mutually restricted. The quality factor is used to comprehensively evaluate the filtration performance of air filtration materials, which is calculated by filtration efficiency and pressure drop. The higher the quality factor value, the better the filtration performance of the filter material. Fig.13 It can be seen that the increase in the amount of PTA added significantly improves the quality factor. It is worth noting that the higher flexibility enables the carbon nanofiber membrane to maintain a higher filtration efficiency. At the same time, the appropriately increased pore size reduces the pressure drop. FCNFM-200 has the highest quality factor of 0.161Pa -1 , which can obviously meet the requirements of high efficiency filtration of PM 0.3 requirements.
[0085] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.
Claims
1. A method for preparing a toughened carbon nanofiber membrane, characterized in that: The method comprises the following steps: firstly, epoxy resin, polyarylene ether nitrile, polyvinyl pyrrolidone, terephthalic acid, carbon nanotubes, polyacrylonitrile and solvent are mixed to prepare a spinning solution, and then electrostatic spinning is performed to obtain a precursor nanofiber membrane; then, the precursor nanofiber membrane is pre-oxidized and then carbonized to obtain a toughened carbon nanofiber membrane.
2. The method for preparing the toughened carbon nanofiber membrane according to claim 1, characterized in that: The mass ratio of epoxy resin, polyarylene ether nitrile, polyvinyl pyrrolidone, terephthalic acid, carbon nanotubes, polyacrylonitrile and solvent is (0.5-2):(1-5):(2-6):(2-7):(0.1-0.5):(5-10):(80-150), and the preferred range is (0.8-1):(1-3):(2-3):(2-3):(0.2-0.3):(7-9):(95-110)。 3. The method for preparing the toughened carbon nanofiber membrane according to claim 1, characterized in that: The molecular weight of polyacrylonitrile is 1×10 5 -2×10 5 ; The solvent is DMF.
4. The method for preparing the toughened carbon nanofiber membrane according to claim 1, characterized in that: The specific method for preparing the spinning solution is: first add carbon nanotubes to the solvent and ultrasonically disperse for 20-50 minutes; then add epoxy resin, polyarylene ether nitrile, polyvinyl pyrrolidone, terephthalic acid and polyacrylonitrile in sequence under constant temperature stirring at 70-90°C, and continue stirring for 2-5 hours.
5. The method for preparing the toughened carbon nanofiber membrane according to claim 1, characterized in that: The conditions for electrospinning are: voltage 15-20 kV, receiving distance 12-20 cm, receiver speed 30-100 rpm, translation speed 80-120 mm / min, stroke 50-150 mm, spinning solution push rate in each syringe 0.5-2 ml / h, temperature 20-35° C., humidity 20-35%.
6. The method for preparing the toughened carbon nanofiber membrane according to claim 1, characterized in that: After the precursor nanofiber membrane is obtained by electrospinning, a drying step is performed, and the drying conditions are: 50-80°C, 10-15h.
7. The method for preparing a toughened carbon nanofiber membrane according to claim 1, characterized in that: The specific method of pre-oxidation is: in air atmosphere, heating to 250-300°C at a heating rate of 0.5-3°C / min, keeping warm for 1-4 hours and then cooling to room temperature; The specific method of carbonization treatment is: in nitrogen or inert gas atmosphere, the temperature is raised to 3-8℃ / min. 320-350℃, keep warm for 1-3h; then heat to 780-850℃ at a heating rate of 3-8℃ / min, keep warm for 1-3h and then cool to room temperature.
8. A toughened carbon nanofiber membrane, characterized in that: The method is prepared by any one of claims 1 to 7.
9. Use of the toughened carbon nanofiber membrane prepared by the method according to any one of claims 1 to 7 in gas purification.
10. A method for increasing the specific surface area and / or the adsorption capacity of VOC and / or the filtration efficiency of PM pollutants of a carbon nanofiber membrane, characterized in that: The method comprises the following steps: firstly, epoxy resin, polyarylene ether nitrile, polyvinyl pyrrolidone, terephthalic acid, carbon nanotubes, polyacrylonitrile and solvent are mixed to obtain a spinning solution, and then electrostatic spinning is performed to obtain a precursor nanofiber membrane; then, the precursor nanofiber membrane is pre-oxidized and then carbonized to obtain a toughened carbon nanofiber membrane; The mass ratio of epoxy resin, poly(arylene ether nitrile), polyvinyl pyrrolidone, terephthalic acid, carbon nanotubes, polyacrylonitrile and solvent is (0.5-2):(1-5):(2-6):(2-7):(0.1-0.5):(5-10):(80-150), and the preferred range is (0.8-1.2):(1-3):(2-4):(2-4):(0.2-0.4):(7-9):(95-110)。
Citation Information
Patent Citations
Multi-hole carbon fiber and preparation method thereof
CN103014921A
Silicon-doped carbon mesoporous composite fiber and preparation method thereof
CN106521720A
Preparation and application of high-strength carbon nano tube-polyacrylonitrile hybrid nanofiber membrane
CN106592110A
Porous carbon nano fiber material for adsorbing carbon dioxide and preparation method thereof
CN107051382A
Preparation method and application of porous carbon nanofiber membrane capable of quickly adsorbing heavy metal ions
CN110158237A